2016
DOI: 10.1039/c6py01144f
|View full text |Cite
|
Sign up to set email alerts
|

ADMET and TAD chemistry: a sustainable alliance

Abstract: Post-polymerisation functionalisation and subsequent crosslinking of unsaturated ADMET derived polymers were performed via the versatile and ultrafast 1,2,4-triazoline-3,5-dione click chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…All modified polymers show an increased T g with ΔT g ranging from 34 to 77°C compared to unmodified polymers, which could be expected from the observations with previously reported polymers after TAD modification. 23 The highest increase of T g was found for the modification with the rigid Ph-TAD, resulting in T g 's of 38°C (C6-Ph), 10°C (C6-Et) and 7°C (C20-Ph). For the two alkyl-containing TADs, the more flexible Oct-TAD shows the lowest effect on the T g 's: 3°C (C6-Ph), −4°C (C6-Et) and 25°C (C20-Ph).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…All modified polymers show an increased T g with ΔT g ranging from 34 to 77°C compared to unmodified polymers, which could be expected from the observations with previously reported polymers after TAD modification. 23 The highest increase of T g was found for the modification with the rigid Ph-TAD, resulting in T g 's of 38°C (C6-Ph), 10°C (C6-Et) and 7°C (C20-Ph). For the two alkyl-containing TADs, the more flexible Oct-TAD shows the lowest effect on the T g 's: 3°C (C6-Ph), −4°C (C6-Et) and 25°C (C20-Ph).…”
mentioning
confidence: 97%
“…They show a similar residual mass at 700°C (Table S3 †) and a similar onset degradation temperature as the unmodified one. From previous studies of TAD derivatives, 23 it is known that the urazole moiety degrades around 300°C (T onset = 250°C) by scission of the carbon-nitrogen linkage to the polymer chain, followed by further degradation to provide aniline and phenyl isocyanate in the gas phase. This indicates that the degradation of the PPE backbone takes place at lower temperatures than the degradation of the TAD moieties, which can explain the limited effect of these nitrogen containing moieties on the thermal degradation of the PPEs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years TAD-(di)ene click reactions were found very useful in the preparation of nanoparticles, 25 polymer bioconjugates synthesis of block co-polymers, 26 functionalization of polymers and materials etc. [27][28][29][30][31][32] In an earlier report, while demonstrating the rst example for the application of 'triazolinedione-ene' reactions to prepare nanoparticles, we have shown that this chemistry can be a useful platform to prepare spherical nanoparticles from multi-ene systems, such as plant oils, via a nanoprecipitation technique. 25 However, such methods cannot be applied for the preparation of asymmetric structures such as Janus particles.…”
Section: Introductionmentioning
confidence: 90%
“…TAD‐based molecules were very reactive toward electron‐rich π‐system and irreversibly reacted fast with dienes and enes to form stable adduct through Diels‐Alder and Alder‐ene mechanisms. A series of researches related to TAD reaction were unfolded by Filip E. Du Prez and coworkers, they investigated a post‐polymerization functionalization for acyclic diene metathesis‐derived polymers with TAD chemistry, and the glass transition temperature ( T g ) of the resulting materials could be tuned by varying conditions . Moreover, TAD click chemistry was applied in constructing sacrificial hydrogen bond into a precrosslinked network, which could eliminate factors that may cause structural changes during rubber vulcanization, and this modification would improve the strength of solution styrene butadiene rubber (SSBR) and endow the modified SSBR with promising triple‐shape memory behavior .…”
Section: Introductionmentioning
confidence: 99%